2013
DOI: 10.1177/0961203313476357
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of renal relapse in Korean patients with lupus nephritis who achieved remission six months following induction therapy

Abstract: Renal relapse in patients with lupus nephritis (LN) is a risk factor for poor renal function. Therefore, there is a need to identify clinical and serological risk factors for renal relapse. A total of 108 patients with LN were enrolled in this study. All the subjects had achieved complete remission or partial remission following six months of induction therapy. We retrospectively analyzed their clinical and laboratory indices, final renal function, and kidney biopsy findings. The median follow-up period after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 39 publications
2
20
1
1
Order By: Relevance
“…Age at onset may also affect renal recurrence. A study conducted in South Korea demonstrated that patients with LN type IV aged <28 years old were more likely to experience renal recurrence (16). However, the results of the present study did not identify an association between age and renal recurrence in patients with LN type IV.…”
Section: Discussioncontrasting
confidence: 99%
“…Age at onset may also affect renal recurrence. A study conducted in South Korea demonstrated that patients with LN type IV aged <28 years old were more likely to experience renal recurrence (16). However, the results of the present study did not identify an association between age and renal recurrence in patients with LN type IV.…”
Section: Discussioncontrasting
confidence: 99%
“…Anti-Ro antibodies in patients with SLE have been associated with neonatal lupus heart block, photosensitivity, and valvular heart disease 2123 . In a study by Moon et al, investigators noted that adult patients with lupus nephritis and anti-Ro antibody had a decreased chance of renal relapse 24 . Another report by Chien et al showed that kidney disease in adults with SLE was associated with absence of anti-Ro antibody, suggesting a protective effect 25 .…”
Section: Discussionmentioning
confidence: 99%
“…No response (NR) was defined as a UPE > 3.5 g/d, or a < 50% reduction in UPE with or without renal deterioration [ 31 ]. Relapse was defined as the reappearance of significant proteinuria, defined as > 1.0 g/d and as a UPE increase of > 50% from the lowest level of proteinuria after remission [ 31 32 ].…”
Section: Methodsmentioning
confidence: 99%